Ocorrência de eventos adversos em hemodiálise sem e com a utilização de duas modalidades de sódio variável: estudo randomizado e com cross-over - Meira, Fernanda Salazar (2009)
Introduction: The most frequent adverse events during dialysis are hypotension (20% to 30%) and muscle cramps (5% to 10%), and the most often prescribed treatment to these adverse events is the use of variable sodium (VNa) profiling. Objectives: The aim of the current study was to compare the frequency of adverse events during hemodialysis (HD), interdialytic weight gain, and blood pressure before and after dialysis, with and without the use of VNa, as well as with the use of two variable sodium models: stepwise (VNass) and linear (VNal). Methods: a randomized, cross-over, prospective study that enrolled 22 patients in two groups: one to receive VNas for 12 HD sessions, and the other VNal, for a similar period after 12 sessions without VNa. After a wash-out period of 12 sessions, groups were crossed over. The following parameters were analyzed: adverse events, interdialytic weight gain, and blood pressure (BP) before and after dialysis. Results: Mean age was 61.2±15.2 years; 11 (50%) patients were male. The occurrence of adverse events was significantly different between the period without VNa (48.5%) and those with VNas and VNal (33.7% and 36%; p<0.001). There were no significant differences in BP or interdialytic weight gain among treatment modalities. Conclusion: The use of VNa was associated with a reduction in the number of adverse events. VNas resulted in less episodes of symptomatic hypotension; while VNal may be associated with reduced muscle cramps. VNa modeling is beneficial for selected patients, and should be individually prescribed.